(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the possession of intermediate school mathematics teachers of visual thinking skills, the researcher adopted the descriptive approach for its suitability to the nature of the research objectives, and prepared a test to find out whether mathematics teachers possess visual thinking skills. The five visual thinking (the skill of shape recognition and description, the skill of shape analysis, the skill of linking information, the skill of perception and interpretation of ambiguity, the skill of extracting meanings), with five paragraphs for each skill, and the validity and stability of the test were verified. After the tool was ready for application, the visual thinking skills test was applied to the research sample (middle school mathematics teachers), in the middle and secondary schools of the General Directorate of Education in Maysan Governorate, then the appropriate statistical analyzes were conducted, and the researcher concluded that middle school mathematics teachers possess visual thinking skills , He also developed a number of conclusions, recommendations and proposals.